Mechanism for the attenuation of neutrophil and complement hyperactivity by MSC exosomes - Loh, Jia Tong (2022)
Complements and neutrophils are two key players of the innate immune system that are widely implicated as drivers of severe COVID-19 pathogenesis, as evident by the direct correlation of respiratory failure and mortality with elevated levels of terminal complement complex C5b-9 and neutrophils. In this study, we identified a feed-forward loop between complements and neutrophils that could amplify and perpetuate the cytokine storm seen in severe SARS-CoV-2-infected patients. We observed for the first time that the terminal complement activation complex C5b-9 directly triggered neutrophil extracellular trap (NET) release and interleukin (IL)-17 production by neutrophils. This is also the first report that the production of NETs and IL-17 induced by C5b-9 assembly on neutrophils could be abrogated by mesenchymal stem cell (MSC) exosomes. Neutralizing anti-CD59 antibodies abolished this abrogation. Based on our findings, we hypothesize that MSC exosomes could alleviate the immune dysregulation in acute respiratory failure, such as that observed in severe COVID-19 patients, by inhibiting complement activation through exosomal CD59, thereby disrupting the feed-forward loop between complements and neutrophils to inhibit the amplification and perpetuation of inflammation during SARS-CoV-2 infection.